2018
DOI: 10.3389/fmars.2018.00198
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Interference and Structural Variation of Quorum Sensing Mimics in Australian Soft Coral

Abstract: Bacterial Quorum Sensing (QS), the indirect regulation of gene expression through production and detection of small diffusible molecules, has emerged as a point of interaction between eukaryotic host organisms and their associated microbial communities. The extracellular nature of QS molecules enables interference in QS systems, in many cases via mimicry. This study targeted QS induction and inhibition in soft coral holobionts, as many soft coral species commonly contain compounds with structural similarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Secondary metabolites from marine organisms are considered an important source of biomolecules for drug discovery (Newman and Cragg, 2004;Borges and Simões, 2019). Bacteria associated with corals, sponges, and other organisms have been recognized as the factual producers of many bioactive compounds (Kelman et al, 2006;Freckelton et al, 2018). Though AHL degradation enzymes from bacterial isolates have been identified from different sources (Dong et al, 2002;Uroz et al, 2003;Ulrich, 2004;Hassan et al, 2016), the investigation of antibiofilm activity of bacteria, particularly from marine resources, are expected to act against antibiotic resistant bacterial pathogens (Huang et al, 2019;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites from marine organisms are considered an important source of biomolecules for drug discovery (Newman and Cragg, 2004;Borges and Simões, 2019). Bacteria associated with corals, sponges, and other organisms have been recognized as the factual producers of many bioactive compounds (Kelman et al, 2006;Freckelton et al, 2018). Though AHL degradation enzymes from bacterial isolates have been identified from different sources (Dong et al, 2002;Uroz et al, 2003;Ulrich, 2004;Hassan et al, 2016), the investigation of antibiofilm activity of bacteria, particularly from marine resources, are expected to act against antibiotic resistant bacterial pathogens (Huang et al, 2019;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with previous studies that reported no clear pattern of QS activity in Vibrionaceae strains, including Vibrio sp. (Tait et al ., 2010; Freckelton et al ., 2018). The AHL production among Pseudomonas and Acinetobacter was much more diverse, with no clear production pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of bacteria that simultaneously emit pro‐ and anti‐QS compounds has been evidenced in a few strains, for example, in Agrobacterium tumefaciens (Zhang et al ., 2004), a marine Shewanella sp. (Tait et al ., 2009), in two isolates related to Endozoicomonas (Freckelton et al ., 2018) or Acinetobacter and Burkholderia strains isolated from the rhizosphere (Chan et al ., 2011). Such co‐occurrence of QS and QQ features in our collection of estuarine strains raises the question of the co‐expression of these two phenotypes, especially within the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…The Gammaproteobacteria class probably contains bacteria with the best-characterized AHL-based QS systems, such as members of the Vibrio, Pseudomonas, and Acinetobacter genera. They are also among the most common AHL producers isolated from various marine habitats (Cuadrado-Silva et al, 2013;Jatt et al, 2015;Freckelton et al, 2018;Charlesworth et al, 2019;Reen et al, 2019;Su et al, 2019;Urvoy et al, 2021a; Supplementary Table 2). In addition, they constitute the main class contributing to AHL production and sensing genes in marine metagenomics surveys, especially members of Vibrionales, Pseudomonadales, or Alteromonadales (Doberva et al, 2015;Huang et al, 2018;Su et al, 2021; Supplementary Table 1).…”
Section: Quorum Sensing and Quorum Quenching Pathwaysmentioning
confidence: 99%
“…Marine Gammaproteobacteria are also actively engaged in AHL-QQ mechanisms involving both QQ enzymes and QSIs. Several studies have reported that isolated marine Gammaproteobacteria strains possess QQ capacities, in which they were often the most represented taxon (Torres et al, 2016;Freckelton et al, 2018;Su et al, 2019;Urvoy et al, 2021a; Supplementary Table 2). In their review, Zhao et al (2019) reported that 27% of marine bacterial isolates with QQ capacities were Gammaproteobacteria.…”
Section: Quorum Sensing and Quorum Quenching Pathwaysmentioning
confidence: 99%